'Google Speak': The discursive practices of search in home-education - Renee Morrison (Dialogic Pedagogy, 2022)
Learning with technology is increasingly understood to be a social process involving unique and telling discourses. An emerging research agenda has resulted, investigating the links between ‘talk’ and student technological practices but is yet to include home-education. Preliminary evidence exists of a relationship between particular types of ‘talk’ and success with particular online activities, namely online search. This may prove especially pertinent to home-educators who report that their most prolific online activities are those reliant upon search engines like Google. This paper presents select findings from a study into online search and the associated discursive practices among early primary students and their parent-educators in Australia. Data from observations, tests and interviews with five home-educating families were analysed recursively using a system guided by Fairclough’s Critical Discourse Analysis.  Specifically, this paper seeks to investigate: which discursive practices are privileged in these sites during online search; the extent to which these practices contribute to relations of power and the extent to which these practices are found alongside effective online search.  Findings revealed a prevalence of inequitable discursive practices, those that either inhibited the equal conversational power of speakers or which naturalised inequitable power relations more generally. These discursive practices were found alongside ineffective online searches. Notwithstanding, participants continued to speak positively about search engines and their educational power. This rhetoric-reality gap is theorized in the paper as the work of dominant ideologies surrounding technology in education.  Findings can assist the growing number of home-educators and their students to use online search more effectively. Insights regarding links between discursive practice and search practice may also help ensure that discourse helps to maximise the educational benefits associated with online search.